Review on risk assessments of dammed lakes - Zhong, Qiming; Wang, Lin; Shan, Yibo; Mei, Shengyao; Zhang, Qiang; Yang, Meng; Zhang, Lucheng; Du, Zhenhan (Frontiers in Earth Science, 2023)
As one type of natural disaster, dammed lakes pose a serious threat to the safety of lives and properties downstream. Scientific risk assessments of dammed lakes are key for pre-disaster prevention and post-disaster rescue. However, due to the lack of basic information and uncertainty surrounding materials and loads, risk assessments of dammed lakes are more complex than those of artificial reservoir dams, and comprehensive assessment methods are lacking. Based on the evolution of dammed lake hazard chains, starting with the concept of a dammed lake risk assessment, this paper focused on six aspects: worldwide dammed lake databases, hazard assessments for landslide dams, breach mechanisms and breach processes, flood routing after landslide dam breaching, loss assessments, and risk mitigation measures. A comprehensive review was conducted on the qualitative and quantitative risk assessment methods around the world, as well as future outlooks.